Efficiency of Social Sector Expenditure in India. - Purohit, Brijesh C. (Routledge, 2014)
Government investments in social sector has always played an important role in tackling social issues and facilitated in the alleviation of poverty. Hence, budgetary expenditure to be mobilized for such investments needs to be efficiently allocated and utilized to maximize the greatest good. This book focuses on the social sector in India and provides an overview of the sector. The book looks at 15 major Indian states between the year 2000-2011 to see how these states had invested in social sector and whether they had met the criteria of efficient social sector investment. Usi.